Features of Technical and Criminalistic Support of Investigative Actions in the Investigation of Crimes Related to Terrorism - CHUKUMOV, Galymzhan Baurzhanovich; DILBARKHANOVA, Zhanat Rakhimzhanovna (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
This article considers the features of technical and criminalistic support of crime scene examination and interrogation at the investigation of crimes related to terrorism. Technical and criminalistic support of investigative actions as a category of criminalistics is widely studied in works of well known criminalistic scientists. However, the features of this category in relation to the investigation of individual crimes, in particular, the act of terrorism, under Article 255 of the Criminal Code of the Republic of Kazakhstan, are not sufficiently studied. At the moment, in the context of the activation of Islamic extremism around the world, the investigative bodies of the Republic of Kazakhstan must be ready to any of its manifestations, so the research conducted in the framework of the present article is very timely and relevant. The aim of this study is to identify and explore the possibilities of technical and criminalistic tools in the investigation of acts of terrorism when carrying out the examination of a crime scene and interrogation. The solution of such problems as the clarification of the essence of the phenomena under consideration and their characteristics, and the optimization of the conceptual apparatus will contribute to the achievement of this aim. The author explores the topic of the crime scene examination and interrogation in the investigation of acts of terrorism, based on the opinions of scholars, legal norms, law enforcement statistics, scientific-practical materials containing the data on the modern technical and criminalistic methods and equipment used in the investigation of acts of terrorism, experience of their application abroad. The author draws a number of important conclusions, in particular, about the necessity for interagency cooperation and involvement in the investigation of a wide range of experts, and puts forward some practical suggestions on the use of technical and criminalistic tools and tactics in the practical activities at the investigation of acts of terrorism.